통합미디어법 도입을 위한 제언 - 유럽연합, 독일, 영국 사례 분석을 중심으로 - 윤장열; Yun Jang-ryol (미디어와 인격권, 2025)
본 연구는 디지털 전환과 플랫폼 경제의 심화 속에서 제기되는 국내 통합미디어법 제정의 필요성과 그 방향성을 고찰한다. 특히 유럽연합의 시청각미디어서비스지침(AVMSD) 개정 과정을 중심으로, 독일과 영국의 미디어 법제 변화 사례를 비교 검토하며, 한국의 신문·방송·정보·통신에 걸친 규제체계가 구조적으로 전환되어야 할 정책적 함의를 도출한다. 기존 미디어 규제는 매체별 이원적 구조에 기반해 상이한 규제 기준을 적용해왔으나, 디지털 플랫폼의 부상은 이러한 수직적 규제를 수평적 규제로 전환할 것을 강하게 요구하고 있다. 이에 따라 본 연구는 통합미디어법이 갖추어야 할 핵심 원칙으로 ‘공공성과 상업성의 균형’, ‘기술 독점에 대한 규제’, ‘플랫폼 공공성의 확보’, ‘공영미디어의 재정립’을 제안한다. 또한, 플랫폼 규제 강화와 디지털 권리 보장을 위한 법제화 방안, 공공 디지털 플랫폼 구축, 통합 규제 기구 설립의 필요성을 제시함으로써, 미디어 법·제도의 전면적 재구성을 위한 규범적·정책적 방향을 제시한다. 본 연구는 지난 15년간 논의에만 머물러온 통합미디어법 제정 논의를 비판적으로 검토하며, 향후 국내 미디어 정책의 체계적 설계를 위한 이론적 토대와 비교법적 시사점을 제공하는 데 목적이 있다. This study explores the necessity and normative direction of introducing a comprehensive media law in South Korea, in response to the structural limitations of the country’s current media regulation amid accelerating digital transformation and the rise of platform-based services. The existing legal framework, fragmented across separate laws for broadcasting, newspapers, telecommunications, and online content, was designed based on a vertically segmented, medium-specific logic that no longer aligns with the realities of a convergent media environment. The increasing dominance of digital platforms and algorithmic content distribution necessitates a shift toward a horizontally integrated regulatory model that can address cross-sectoral challenges. Through a comparative legal analysis, this study examined the European Union’s revised Audiovisual Media Services Directive as a foundational reference point while drawing on legislative developments in Germany and the United Kingdom. These cases offer practical insights into how regulatory regimes can evolve to manage digital convergence, platform accountability, and the preservation of public values in increasingly commercialized and data-driven media ecosystems. Based on this comparative inquiry, the study proposes four normative principles that should guide the formation of a comprehensive media law in South Korea: (1) the balancing of public interest with commercial sustainability; (2) effective regulation of technological and economic monopolies; (3) safeguarding of digital publicness as a democratic imperative; and (4) redefinition of public service media in a platform-centric context. Additionally, this research outlines institutional and legal recommendations, including the establishment of a unified media regulatory authority, enhanced transparency and accountability obligations for digital platforms, strengthened digital rights protections for users, and the development of public digital infrastructure. By addressing the 15-year legislative stagnation surrounding media reform in Korea, this study offers a theoretical foundation and comparative policy insights for reconfiguring national media governance in a way that is future-oriented, democratically grounded, and responsive to the challenges of the digital era.